Methods in food analysis - Rui M S Cruz (CRc, 2014)
"The book reviews methods of analysis and detection in the area of food science and technology. There are seven chapters, each dealing with the determination/quantification analyses of quality parameters in food which cover topics such as lipids, color, texture, and rheological properties in different food products. The book focuses on the most common methods of analysis, presenting methodologies with specific work conditions. It will serve as a source of reference for universities, food engineers and researchers from R&D laboratories working in the area of food science and technology. Students at undergraduate and postgraduate levels in food science and technology will also benefit from the book"--